PROBLEMS OF TRAINING TECHNOLOGY TEACHERS IN UZBEKISTAN (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The modernization of teacher education in Uzbekistan represents one of the most strategically significant directions of national reform, as it determines the quality of future generations’ technical literacy, creativity, and socio-economic competence. This study investigates the systemic, methodological, and institutional problems in the preparation of technology teachers within Uzbekistan’s higher pedagogical education system. The research applies a comprehensive analytical framework integrating competence-based, system-structural, and constructivist approaches to explore how teacher training programs meet the demands of the 21st century. Using documentary analysis, comparative studies, and field surveys, the paper identifies critical deficiencies in curriculum design, pedagogical practice, material-technical infrastructure, and digital literacy training. Empirical data collected from 12 pedagogical universities and 248 teacher trainees demonstrate that the current system remains largely oriented toward reproductive knowledge rather than transformative, design-based learning. The findings reveal key obstacles: outdated curricula, insufficient STEAM integration, limited access to technological laboratories, weak coordination between industry and education, and inadequate methodological training for practice-based innovation. Based on these results, the study proposes a competency-driven model for teacher training that emphasizes technological creativity, interdisciplinary integration, digital pedagogy, and continuous professional development. Ultimately, the paper concludes that reforming technology teacher education is not simply an academic necessity but a national imperative for ensuring sustainable technological advancement and labor market competitiveness in Uzbekistan.